Effect of cytosine–Ag+–cytosine base pairing on the redox potential of the Ag+/Ag couple and the chemical reduction of Ag+ to Ag by tetrathiafulvalene. Issue 22 (11th May 2021) - Dairaku, Takenori; Kawai, Rika; Kanaba, Teppei; Ono, Tetsuya; Yoshida, Kentaro; Sato, Hajime; Nozawa-Kumada, Kanako; Kondo, Yoshinori; Kondo, Jiro; Ono, Akira; Tanaka, Yoshiyuki; Kashiwagi, Yoshitomo
Abstract : [Ag(cytidine)2 ] + formation can be utilized for controlling the redox potential of the Ag + /Ag couple. Abstract : The redox properties of metallo-base pairs remain to be elucidated. Herein, we report the detailed 1 H/ 13 C/ 109 Ag NMR spectroscopic and cyclic voltammetric characterisation of the [Ag(cytidine)2 ] + complex as isolated cytosine–Ag + –cytosine (C–Ag + –C) base pairs. We also performed comparative studies between cytidine/Ag + and other nucleoside/Ag + systems by using cyclic voltammetry measurements. In addition, to evaluate the effect of [Ag(cytidine)2 ] + formation on the chemical reduction of Ag + to Ag, we utilised the redox reaction between Ag + and tetrathiafulvalene (TTF). We found that Ag + -mediated base pairing lowers the redox potential of the Ag + /Ag couple. In addition, C–Ag + –C base pairing makes it more difficult to reduce captured Ag + ions than in other nucleoside/Ag + systems. Remarkably, the cytidine/Ag + system can be utilised to control the redox potential of the Ag + /Ag couple in DMSO. This feature of the cytidine/Ag + system may be exploited for Ag nanoparticle synthesis by using the redox reaction between Ag + and TTF.